Evaluación de la crioconservación del semen de Cobayo (Cavia Porcellus) en el Laboratorio de Biotecnología de la Reproducción de la Carrera de Medicina Veterinaria de la Universidad Técnica de Cotopaxi - Mise Chango, Mayra Nataly (2014)
The evaluation of the cryopreservation semen from Guinea pig was conducted in the laboratory of biotechnology of reproduction of the career of veterinary medicine of the Technical University of Cotopaxi. The main objective was to establish and evaluate a cryopreservation protocol that maintains cell viability and functionality for an extended period of time. To perform the evaluation of the test samples for both seminal assessment cool and postthawed semen was performed, was valued following parameters: color, pH, concentration, mortality, mobility and morphology. 10 guinea pigs adult males who were physically and then slaughtered evaluated half hour then proceeded to perform the removal of testicles castration, semen was collected by the method of dissection and washing testes were used to then be filled in straws and frozen in liquid nitrogen at -196 ° C.